2014
DOI: 10.1016/j.neuropharm.2013.04.058
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic synaptic plasticity in developing spinal networks driven by excitatory GABAergic currents

Abstract: Homeostatic plasticity refers to mechanisms that the cell or network engage in order to homeostatically maintain a preset level of activity. These mechanisms include compensatory changes in cellular excitability, excitatory and inhibitory synaptic strength and are typically studied at a developmental stage when GABA or glycine are inhibitory. Here we focus on the expression of homeostatic plasticity in the chick embryo spinal cord at a stage when GABA is excitatory. When spinal activity is perturbed in the liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 89 publications
1
22
0
Order By: Relevance
“…Under chronic suppression of neuronal activity, HSP is expressed via an increase in synaptic expression of AMPARs producing an up-scaling of AMPAR-mediated miniature post-synaptic currents (mEPSCs). While most studies show inactivity-induced synaptic scaling in cultured neurons [2, 46, 50, 55], HSP is also observed in vivo including in the spinal cord [16, 19, 33, 59] and in the visual cortex [11, 17, 31, 34, 38]. AMPARs are heterotetrameric ion channels consisting of different compositions of the four subunits GluA1–4, and the most common of which are GluA1/GluA2 and GluA2/GluA3 combinations [5, 13].…”
Section: Introductionmentioning
confidence: 99%
“…Under chronic suppression of neuronal activity, HSP is expressed via an increase in synaptic expression of AMPARs producing an up-scaling of AMPAR-mediated miniature post-synaptic currents (mEPSCs). While most studies show inactivity-induced synaptic scaling in cultured neurons [2, 46, 50, 55], HSP is also observed in vivo including in the spinal cord [16, 19, 33, 59] and in the visual cortex [11, 17, 31, 34, 38]. AMPARs are heterotetrameric ion channels consisting of different compositions of the four subunits GluA1–4, and the most common of which are GluA1/GluA2 and GluA2/GluA3 combinations [5, 13].…”
Section: Introductionmentioning
confidence: 99%
“…Although less studied, activity-dependent plasticity also plays a role in more intact embryonic spinal cord preparations in vitro at a time when GABAergic and glycinergic NT evoked currents and are considered depolarizing and excitatory (for reviews see Wenner, 2013; Momose-Sato and Sato, 2013). One of the first experiments to explore the pharmacological details of rSNA, as well as the potential for activity dependent plasticity, was Chub and O’Donovan (1998), who showed that the combined inhibition of glutamatergic and cholinergic NT in the E10–11 chick lumbar spinal cord produced a strengthening of GABAergic and glycinergic NT.…”
Section: Discussionmentioning
confidence: 99%
“…The myriad of potential mechanisms responsible for the self-regulation of embryonic rSNA can be broadly grouped as increases and/or decreases in cellular/network excitability and or alterations in synaptic strength (Lindsly et al, 2014; Gonzalez-Islas et al, 2009; for review see Wenner, 2013). Although we have not determined mechanism by which GABAergic/glycinergic NT is potentiated by the loss of rSNA, we speculate that both the absence of nicotinic-evoked inward currents and the low [K + ] o perturbation increased the strength of GABAergic/glycinergic NT in the following way: we propose that the observed strengthening of Cl − -mediated conductance and depolarization is likely a straightforward result of the prolonged cessation of action potential generation, as others have previously shown in the spinal cord (Lindsly et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was first described in pioneering theoretical studies and experimental work employing neurons isolated from the stomatogastric nervous system of crustaceans. Such homeostatic plasticity has now been observed and modeled in cell culture, brain slices and in vivo across invertebrates and vertebrates and has led to important concepts such as synaptic scaling (Davis 2006; LeMasson et al 1993; Turrigiano 2007; Wenner 2014). An evolving notion is that intracellular [Ca 2+ ] -- fed by Ca 2+ entry through voltage-gated Ca 2+ channels or Ca 2+ -permeable synaptic channels --serves as an effective signal of neuronal and network activity (Liu et al 1998; Turrigiano 2007).…”
mentioning
confidence: 99%